Cold‐Season Arctic Amplification Driven by Arctic Ocean‐Mediated Seasonal Energy Transfer. Issue 2 (28th January 2021) - Chung, Eui‐Seok; Ha, Kyung‐Ja; Timmermann, Axel; Stuecker, Malte F.; Bodai, Tamas; Lee, Sang‐Ki
Abstract: The Arctic warming response to greenhouse gas forcing is substantially greater than the rest of the globe. It has been suggested that this phenomenon, commonly referred to as Arctic amplification, and its peak in boreal fall and winter result primarily from the lapse‐rate feedback, which is associated with the vertical structure of tropospheric warming, rather than from the sea‐ice albedo feedback, which operates mainly in summer. However, future climate model projections show consistently that an overall reduction of sea‐ice in the Arctic region leads to a gradual weakening of Arctic amplification, thereby implying a key role for sea‐ice albedo feedback. To resolve this apparent contradiction, we conduct a comprehensive analysis using atmosphere/ocean reanalysis data sets and a variety of climate model simulations. We show that the Arctic Ocean acts as a heat capacitor, storing anomalous heat resulting from the sea‐ice loss during summer, which then gets released back into the atmosphere during fall and winter. Strong air‐sea heat fluxes in fall/winter in sea‐ice retreat regions in conjunction with a stably stratified lower troposphere lead to a surface‐intensified warming/moistening, augmenting longwave feedback processes to further enhance the warming. The cold‐season surface‐intensified warming/moistening is found to virtually disappear if ocean‐atmosphere‐sea ice interactions are suppressed, demonstrating the importance of ice insulation effect and ocean heat uptake/release. These results strongly suggest that the warm‐season ocean heat recharge and cold‐season heat discharge link and integrate the warm and cold season feedbacks, and thereby effectively explain the predominance of the Arctic amplification in fall and winter. Plain Language Summary: The Arctic warms faster than the rest of our planet. Interestingly, this accelerated warming is most pronounced in boreal fall and winter, when the sea‐ice albedo feedback is not active due to a lack of sunshine, which has led numerous studies to emphasize the role of longwave feedback processes. Here, we present observational and modeling evidence that the seasonal evolution of Arctic amplification cannot be explained by a single mechanism such as lapse‐rate feedback or sea‐ice albedo feedback. We show that ocean‐atmosphere heat exchanges associated with sea‐ice reduction are essential for Arctic amplification and its seasonality. In particular, our analysis shows that the ocean heat capacitor mechanism links and integrates the warm and cold season feedbacks, thereby explaining the seasonal evolution of Arctic amplification, and its peak in the cold season. This connected nature of climate feedback processes in conjunction with insulation effect of sea ice implies a substantial weakening of Arctic amplification and its seasonal contrast in a future ice‐free climate as well as during ice‐free states in the geological past. Key Points: Arctic warming amplification and its peak in fall and winter cannot be explained by a single mechanism such as lapse‐rate feedback Positive local longwave feedback processes in fall and winter are intricately linked to ocean‐to‐atmosphere heat and moisture fluxes The cold‐season peak can be explained by the ocean heat capacitor mechanism that links and integrates the warm and cold season feedbacks